Contested boundaries: consensus and dissensus in European attitudes to immigration. Issue 3 (17th February 2020) - Heath, Anthony F.; Richards, Lindsay
ABSTRACT: The paper explores differences in attitudes towards immigration both between and within countries. We draw on new questions, included in the ESS for the first time in 2014, about willingness to accept culturally distinct groups of migrants such as Muslims. These new measures yield additional insights about the nature of symbolic boundaries since they directly tap one of the most salient boundaries in contemporary migration discourse. The paper makes use of Multilevel Latent Class Analysis, a method enabling one to disentangle group-level from individual-level differences. The findings distinguish three classes of individual attitudes, labelled 'restrictive', 'selective' and 'open'. The proportions of individuals belonging to these classes varies across European countries, which fit into three more or less distinct sets (labelled the Czech model, the Norway model and the Ireland model). These three sets display differing levels of internal homogeneity, with the Czech model being the most homogeneous and the Norway model the most heterogeneous. This pattern is also reflected in the degree of socio-economic polarisation. In effect, the nature of the symbolic boundaries are more contested within the Ireland and Norway models, different groups having very different ideas of where the boundaries lie and how rigid they should be.